THE POWER OF SOCIAL MEDIA MARKETING AS INFORMATION TECHNOLOGY FOR TOURISM INDUSTRY REVITALIZATION: STUDY ON INDONESIAN SMES AGROTOURISM - Supriono; Irawan, Ari Irawan; Wiyata; Ramadhani, Zaki Alif (Veredas do Direito, 2025)
Purpose –The purpose of this study is to investigate the impact of social media marketing on the revitalization of the tourism industry in Indonesia, with a specific focus on the role of small and medium-sized enterprises (SMEs) in agrotourism. Design/methodology – A quantitative approach was used, quantitative data collected through online surveys distributed to SMEs involved in agrotourism in the East Java Province, Indonesia. Findings – This study highlights the significance of perceived quality in enhancing the repurchase intention of SMEs Agrotourism products in East Java Province, Indonesia. While Social Media Marketing (SMM) influences perceived quality and price fairness, it's only perceived quality that acts as a mediator between SMM and repurchase intention. The findings highlight the importance of concentrating on improving perceived quality through effective SMM strategies, ensuring that products and services possess quality, value, and fair pricing to elevate repurchase intention. Originality –This study is one of the first to explore the role of social media marketing in the revitalization of the tourism industry in Indonesia, with a particular emphasis on agrotourism and SMEs. It provides insights for policymakers, tourism marketers, and SMEs on the importance of social media as a promoting tool agrotourism and rebuilding tourism industry in rural area.